KEDUDUKAN KETURUNAN CUCU AHLI WARIS YANG TIDAK MENDAPATKAN HARTA WARIS PURUSA DALAM ADAT BALI (STUDI PUTUSAN NOMOR 206/PDT.G/2019/PN AMP): Position of Descendants of Heirs and Grandchildren Who Did Not Get The Inheritance in Balinese Traditional Heir (Study Of Decision Number 206/Pdt. G/2019/Pn Amp) - Yulian, Ilham; Suka'arsana, I Komang (AMICUS CURIAE, 2024)
Bali, where the majority of the population is Hindu, in terms of inheritance, still adheres to customary law whereas Balinese people still adhere to the patrilineal system, namely boys are purusa in terms of inheritance. The issue raised is how the position of the descendants of the heirs' grandchildren towards the inheritance in the Balinese Indigenous people and whether the content of decision number 206/Pdt.G/2019/PN Amp is by the distribution of inheritance in the Balinese Indigenous people. The type of research used is juridical-normative which is descriptive by using secondary data that is analyzed qualitatively. Based on the results of the analysis on the Balinese indigenous people, if the heir does not have descendants, then the one who has the right to return to the inheritance property should be the heir's parents (if there is still one), but when the heir's parents are no longer there, the one who has the right to inherit is the Purusa brothers of the heir who has descendants (as a successor heir). The contents of Decision Number 206/Pdt.G/2019/PN Amp are not in accordance with the distribution of inheritance in the Balinese Indigenous People, because the heirs who get the inheritance from the heirs are the heirs who do not have a purusa line, namely the cultivators of the land, even though the heirs should be the descendants of the relatives of the heirs as the successor heirs.